Optical Techniques for Detecting and Identifying Biological-Warfare Agents - Greenwood, Darryl P.; Jeys, Thomas H.; Johnson, Bernadette; Richardson, Jonathan M.; Shatz, Michael P. (Proceedings of the IEEE, 2009)
Rapid and accurate detection and identification of biological agents is an objective of various national security programs. Detection in general is difficult owing to natural clutter and anticipated low concentrations of subject material. Typical detection architectures comprise a nonspecific trigger, a rapid identifier, and a confirming step, often in a laboratory. High-confidence identification must be made prior to taking action, though this must be traded against regrets stemming from delay. Sensing requirements are best established by positing plausible scenarios, two of which are suggested herein. Modern technologies include the use of elastic scatter and ultraviolet laser-induced fluorescence for triggering and standoff detection. Optical and nonoptical techniques are used routinely in analyzing clinical samples used to confirm infection and illness resulting from a biological attack. Today, environmental sensing serves at best as an alert to medical authorities for possible action, which would include sample collection and detailed analysis. This paper surveys the state of the art of sensing at all levels.